2021
DOI: 10.1038/s41386-021-01131-1
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal-hippocampal interactions supporting the extinction of emotional memories: the retrieval stopping model

Abstract: Neuroimaging has revealed robust interactions between the prefrontal cortex and the hippocampus when people stop memory retrieval. Efforts to stop retrieval can arise when people encounter reminders to unpleasant thoughts they prefer not to think about. Retrieval stopping suppresses hippocampal and amygdala activity, especially when cues elicit aversive memory intrusions, via a broad inhibitory control capacity enabling prepotent response suppression. Repeated retrieval stopping reduces intrusions of unpleasan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 153 publications
3
35
0
1
Order By: Relevance
“…One of the proposed explanations for these null findings is that the formation and processing of memories may be highly heterogenous across participants (Hirst et al, 2009). For instance, some participants may rehearse or reactivate their memories in between encoding and testing, which is known to modulate (autobiographical) memory accessibility (Nadel et al, 2007) or, in contrast, try to stop any retrieval of unpleasant memories (Anderson & Floresco, 2022). Our findings underscore that it is additionally important to consider what components of memory are being assessed, as central memories can be enhanced but contextual elements may be impaired for emotional events (e.g., Brewin et al, 2010; Elzinga & Bremner, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…One of the proposed explanations for these null findings is that the formation and processing of memories may be highly heterogenous across participants (Hirst et al, 2009). For instance, some participants may rehearse or reactivate their memories in between encoding and testing, which is known to modulate (autobiographical) memory accessibility (Nadel et al, 2007) or, in contrast, try to stop any retrieval of unpleasant memories (Anderson & Floresco, 2022). Our findings underscore that it is additionally important to consider what components of memory are being assessed, as central memories can be enhanced but contextual elements may be impaired for emotional events (e.g., Brewin et al, 2010; Elzinga & Bremner, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal LPS exposure produces profound alterations in microglial morphology in the PFC in middle-aged male and female rats, indicating an activated state, and an effect that was evident months after challenge. In adult male rats, studies show that 24 h after exposure to a low to moderate dose, LPS increases microglial activity in the PFC [ 19 , 34 ], a brain region that plays a significant role in cognitive performance [ 35 , 36 ]. Notably, activated microglia, specifically in the cortex, associated with inflammatory insult during early postnatal development in rodents, is influenced by CXCL1 signaling [ 37 ], suggesting a role for brain chemokines in microglial activation.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have shown that prefrontal regions are engaged during retrieval inhibition and that they modulate the activity of downstream areas (Anderson and Floresco, 2021). Interestingly, functional homologous regions in rodents, like the mPFC, have also been associated with retrieval inhibition (Bekinschtein et al, 2018).…”
Section: Discussionmentioning
confidence: 99%